An algebra problem by A Former Brilliant Member

Algebra Level pending

If x = ( 13 + 11 ) 6 x= \left(\sqrt {13}+\sqrt {11}\right)^6 , find the value of x ( 1 { x } ) x(1-\{x\}) .

Notation: { } \{ \cdot \} denotes the fractional part function .


The answer is 64.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Feb 25, 2020

Write x = ( 13 + 11 ) 6 = j = 0 6 ( 6 j ) 1 3 6 j 2 1 1 j 2 y = ( 13 11 ) 6 = j = 0 6 ( 1 ) j ( 6 j ) 1 3 6 j 2 1 1 j 2 x + y = j = 0 6 ( 1 + ( 1 ) j ) ( 6 j ) 1 3 6 j 2 1 1 j 2 = 2 j = 0 3 ( 6 2 j ) 1 3 3 j 1 1 j \begin{aligned} x & = \; \big(\sqrt{13} + \sqrt{11}\big)^6 \; = \; \sum_{j=0}^6 \binom{6}{j} 13^{\frac{6-j}{2}} 11^{\frac{j}{2}} \\ y & = \; \big(\sqrt{13} - \sqrt{11}\big)^6 \; = \; \sum_{j=0}^6 (-1)^j\binom{6}{j} 13^{\frac{6-j}{2}} 11^{\frac{j}{2}} \\ x + y & = \; \sum_{j=0}^6 \big(1 + (-1)^j\big)\binom{6}{j} 13^{\frac{6-j}{2}} 11^{\frac{j}{2}} \; = \; 2\sum_{j=0}^3 \binom{6}{2j} 13^{3-j} 11^j \end{aligned} so that x + y x +y is an integer while 0 < y < 1 0 < y < 1 . Thus { x } = 1 y \{x\} = 1 - y , and hence x ( 1 { x } ) = x y = [ ( ( 13 + 11 ) ( 13 11 ) ] 6 = 2 6 = 64 x\big(1- \{x\}\big) \; = \; xy \; = \; \big[(\big(\sqrt{13}+\sqrt{11}\big)\big(\sqrt{13}-\sqrt{11}\big)\big]^6 \; = \; 2^6 \; = \; \boxed{64}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...